Da'wah bil Social Media: A Phenomenological Study of iGeneration TikTok Platform Users - Nasution, Nadya Amalia (Universitas Sang Bumi Ruwa Jurai, 2024)
This research examines the phenomenon of da'wah through social media (social media) carried out by iGeneration, especially UIN Raden Intan Lampung students, who are users of the TikTok platform. By using a phenomenological approach and integrating the Stimulus-Organism-Response (SOR) theory with the concept of social media